INTENSIFIKASI KOMPETENSI PAJAK PADA RELAWAN PAJAK DI UNIVERSITAS TERBUKA - Ridha Azka Raga; Syafiqoh Nurhayati; Husna Putri Pertiwi; Jasrial Jasrial; Syarif Fadillah; Agus Santosa; Dedy Juniadi (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
This study aims to determine the role of the Tax Center at Universitas Terbuka and the intensification of competence for tax volunteers before being deployed to taxpayers in assisting activities in filling out tax returns. This research was conducted through a qualitative method by presenting descriptive data obtained from literature studies and observations at the Tax Center Universitas Terbuka. Intensification is held by providing training materials, namely: Communication and Leadership, Tax Awareness and Annual SPT, Completing Annual Individual SPTs, and Code of Conduct. In addition, webinars, sharing sessions, and literacy clubs are held. All of these activities are a form of Pengabdian Masyarakat as part of Tridharma Perguruan Tinggi and establish synergy with the Banten Regional Office of the Directorate General of Taxes. Based on the evaluation results of Taxpayers who receive assistance from Tax Volunteers, they are satisfied with the services provided by Tax Volunteers, both from their role in providing assistance and also from the way they communicate with Taxpayers, which is considered helpful with the existence of Tax Center activities and hoping that the activities consistently exist annually. Keywords: Tax Competency Intensification; Tax Center; Tax Volunteers.